Religion, Age, and Sexuality: An Empirical Approach to the Regulation of Female Sexuality through Dress among Indonesian Muslims - Shin, Jiwon (Religions, 2024)
This study investigated how religious factors exert social pressure to discipline female bodies through hijab practices in Indonesia. This study identified relationships among factors, such as religiosity, individuals’ involvement with religious communities, subjective norms regarding the hijab practice, and the regulation of sexuality. This study found that religious factors positively influence subjective norms which reinforce the regulation of sexuality. Although recent studies have underscored the role of the hijab as a tool for expressing Muslim identity and as a means for Muslim women to construct modernity, the results of this study reveal that the disciplinary function of the hijab still seems to have a greater impact. A group analysis reveals differences in the influence of religious factors on subjective norms. While religiosity has a larger impact among adolescents than their involvement with religious communities, this impact is insignificant in the age group of 20s and 30s. The varying effects of religious factors among different age groups imply that religious values rather than involvement with religious communities have a much greater impact on the construction of subjective norms among adolescents while the role of religion in socialization might be enhanced as individuals get older.